Circulating prosaposin and ependymin-related protein 1 levels are correlated with insulin resistance in type 2 diabetic patients - Xin Ji; Xin Ji; Yajing Wang; Yajing Wang; Sijia Xu; Sijia Xu; Ling Cao; Ling Cao; Penghua Fang; Zhenwen Zhang; Zhenwen Zhang (Frontiers in Endocrinology, 2025)
ObjectiveSkeletal muscle and adipose tissues secrete myokines and adipokines to regulate energy metabolism. Experimental evidence indicates that prosaposin (PSAP) and ependymin-related protein 1 (EPDR1) are involved in the regulation of thermogenesis and energy metabolism. To our knowledge, little literature has been found dealing with PSAP and EPDR1 levels in type 2 diabetes mellitus (T2DM) patients. The aim of the study was to evaluate possible relationships between both peptide levels and insulin resistance indexes in type 2 diabetic subjects.MethodsThe study groups consisted of 64 T2DM subjects and 22 normal controls. Serum PSAP and EPDR1 concentrations were determined using immunosorbent assay kits.ResultsThe serum PSAP (319.6 ± 78.38 vs. 207.2 ± 42.43, P<0.0001) and EPDR1 (7.988 ± 3.484 vs. 6.399 ± 3.788, P=0.0823) concentrations were higher in T2DM subjects than normal controls. In addition, positive correlations were found between: PSAP and fasting blood glucose (FBG) levels (r = 0.5004; P< 0.0001), PSAP and Hemoglobin A1c (HAb1c) (r = 0.4688; P< 0.0001), PSAP and C-peptide (r = 0.3981; P = 0.0003), PSAP and triglyceride-glucose index (TyG) (r = 0.2362; P< 0.0001), PSAP and homeostasis model assessment of insulin resistance (HOMA-IR) (r = 0.3314; P = 0.0035), PSAP and homeostasis model assessment of C-peptide resistance (HOMA-CR) (r = 0.5486; P< 0.0001), EPDR1 and insulin (r = 0.2291; P = 0.045), EPDR1 and HOMA-IR (r = 0.2462; P = 0.0309) in both T2DM and normal control subjects.ConclusionsOur results indicated that T2DM individuals have higher serum PSAP and EPDR1 levels, and both peptide concentrations were positively correlative to insulin (INS) resistance levels. PSAP and EPDR1 levels may be taken as potential biomarkers to forecast the development of T2DM.